Epileptic spasms in epilepsy with myoclonic‐atonic seizures (Doose syndrome). Issue 3 (9th September 2016) - Pittau, Francesca; Korff, Christian M.; Nordli, Douglas R.
Abstract: Aim . To describe the occurrence of epileptic spasms in epilepsy with myoclonic‐atonic seizures (EMAS) or Doose syndrome. Methods . Case descriptions of patients with EMAS and epileptic spasms. Diagnosis of EMAS was performed according to the following criteria: (1) onset of myoclonic, myoclonic‐atonic, or atonic seizures at between 7 months and 6 years of age; (2) normal development before onset of epilepsy; (3) absence of structural cerebral abnormalities on MRI; (4) presence of generalized spike‐waves or polyspike‐waves on EEG; and (5) exclusion of other myoclonic epilepsies. Results . Four patients with EMAS were included. For each of them, epileptic spasms were documented by video interpretation, or video‐EEG when available. Conclusions . Our description of epileptic spasms in four patients with EMAS enlarges the spectrum of seizures that may be observed in this syndrome, as well as the number of epilepsy syndromes which may involve epileptic spasms. This evidence suggests that the presence of epileptic spasms is consistent with a diagnosis of EMAS; epileptic spasms should therefore not be considered a seizure type that excludes diagnosis of this epilepsy syndrome. The prognostic significance of epileptic spasms associated with EMAS remains unknown.